Предмет: Алгебра, автор: gluskovaanastasia998


(6x - 3) \times ( - x - 7) = 0


NNNLLL54: 1/2 , -7

Ответы

Автор ответа: polina2005io1113
1

6x-3=0                                                  -6x^{2} -42x+3x+21=0\\-6x^{2} -39x+21=0\\2x^{2} +13x-7=0\\\\x1=\frac{-13+15}{4} \\x2=\frac{-13-15}{4} \\\\

-x-7=0                                                  

x1=\frac{1}{2}     или 0,5                               x1=\frac{1}{2}     или 0,5                              

x2=-7

x2=-7                                              x2=-7

Смотря каким методом вы решаете.

Похожие вопросы